Trade in Pottery within the Lower Adriatic in the 2nd century BCE - De Mitri , Carlo (Journal of Hellenistic Pottery and Material Culture, 2016)
Material culture represents one of the tangible traces to attest to the extensive network of contacts and activities that blossomed over the distinct historical ages among peoples and populations residing in different geographical areas.